The Metallurgy of Anodizing Aluminum Connecting Science to Practice - Runge, Jude Mary (Springer International Publishing, 2018)
In this book, the history of the concepts critical to the discovery and development of aluminum, its alloys and the anodizing process are reviewed to provide a foundation for the challenges, achievements, and understanding of the complex relationship between the aluminum alloy and the reactions that occur during anodic oxidation. Empirical knowledge that has long sustained industrial anodizing is clarified by viewing the process as corrosion science, addressing each element of the anodizing circuit in terms of the Tafel Equation. This innovative approach enables a new level of understanding and engineering control for the mechanisms that occur as the oxide nucleates and grows, developing its characteristic highly ordered structure, which impact the practical function of the anodic aluminum oxide. Addresses anodizing as a metallurgical process, in terms of corrosion science; Presents an innovative mechanism for the formation of the characteristic highly ordered structure of the anodic oxide; Details the importance of the association between aluminum manufacturing and anodizing for practical applications; Provides case studies that show the connection between the aluminum microstructure and the anodic aluminum oxide.